2018
DOI: 10.24052/jbrmr/v12is03/art-15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social entrepreneurship pedagogical initiatives on students’ attitudes and behaviours

Abstract: This study examines the influence of social entrepreneurship pedagogy on the behavioural outcomes of the Nigerian universities' students; regarding their attitudes, intentions and behaviours towards social venture creation. The Nigeria university system is producing graduates as employees rather than employers of labour. Insights were drawn from the theory of planned behaviour and theory 'U' in this inquiry. The principles of quantitative and correlational methods were combined in an explanatory research desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The traditional way in which universities may affect the SEI of students is through the offering of social entrepreneurship education programs. The impact of social entrepreneurship education programs on the precursors of the SEI of students has been the subject of several studies in the past (Adelekan et al, 2018;Hockerts, 2017;Kedmenec et al, 2017;Kwong et al, 2012;Piperopoulos & Dimov, 2015;Smith & Woodworth, 2012;Tshikovhi & Shambare, 2015). The investigation of other aspects of the university's ESS such as business incubation and spin-offs (Chiesa & Piccaluga, 2000;Hughes, Ireland, & Morgan, 2007;Markuerkiaga, Caiazza, Igartua, & Errasti, 2016;Mian, 1996Mian, , 1997, technology transfer mechanisms (Bray & Lee, 2000;Etzkowitz, 2003;Poole & Robertson, 2003), university venture funds (Lerner, 2004) and mentoring and networking (Nielsen & Lassen, 2012) are less common in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The traditional way in which universities may affect the SEI of students is through the offering of social entrepreneurship education programs. The impact of social entrepreneurship education programs on the precursors of the SEI of students has been the subject of several studies in the past (Adelekan et al, 2018;Hockerts, 2017;Kedmenec et al, 2017;Kwong et al, 2012;Piperopoulos & Dimov, 2015;Smith & Woodworth, 2012;Tshikovhi & Shambare, 2015). The investigation of other aspects of the university's ESS such as business incubation and spin-offs (Chiesa & Piccaluga, 2000;Hughes, Ireland, & Morgan, 2007;Markuerkiaga, Caiazza, Igartua, & Errasti, 2016;Mian, 1996Mian, , 1997, technology transfer mechanisms (Bray & Lee, 2000;Etzkowitz, 2003;Poole & Robertson, 2003), university venture funds (Lerner, 2004) and mentoring and networking (Nielsen & Lassen, 2012) are less common in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…This process revealed that no previous researcher has considered the SEI of students as influenced by the university's ESS per se. Some researchers who studied the influence of the university on the SEI of students did so in relation to the effect of social entrepreneurship education (Adelekan, Williamson, & Atiku, 2018;Kedmenec, Rebernik, & Tominc, 2017;Kwong, Thompson, & Cheung, 2012;Piperopoulos & Dimov, 2015;Smith & Woodworth, 2012;Tshikovhi & Shambare, 2015). Thus, the authors modified the inclusion criteria to contain articles that deal with the SEI of students in more general terms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations